2018
DOI: 10.1016/j.ijpddr.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic drug actions in resistant and susceptible C. elegans revealed by electrophysiological recordings in a multichannel microfluidic device

Abstract: Many anthelmintic drugs used to treat parasitic nematode infections target proteins that regulate electrical activity of neurons and muscles: ion channels (ICs) and neurotransmitter receptors (NTRs). Perturbation of IC/NTR function disrupts worm behavior and can lead to paralysis, starvation, immune attack and expulsion. Limitations of current anthelmintics include a limited spectrum of activity across species and the threat of drug resistance, highlighting the need for new drugs for human and veterinary medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 112 publications
(208 reference statements)
4
41
0
Order By: Relevance
“…indicates that higher intestinal exposure increases the overall dose of IVM. Although the uptake capacities cannot be directly quantified, elegans bus-8 loss-of-function strain (53). In line with the findings of this study, a study by O'Lone and Campbell indicated that PP inhibition by refrigeration and thus inhibition of oral ingestion reduced the susceptibility to IVM in C. elegans (54).…”
Section: Discussionsupporting
confidence: 80%
“…indicates that higher intestinal exposure increases the overall dose of IVM. Although the uptake capacities cannot be directly quantified, elegans bus-8 loss-of-function strain (53). In line with the findings of this study, a study by O'Lone and Campbell indicated that PP inhibition by refrigeration and thus inhibition of oral ingestion reduced the susceptibility to IVM in C. elegans (54).…”
Section: Discussionsupporting
confidence: 80%
“…Many screens (although not all ( Weeks et al, 2018 )) to identify anthelmintic products rely on whole-worm motility assays to assess efficacy. While important, immotility is a non-specific outcome that may result from many different causes.…”
Section: Introductionmentioning
confidence: 99%
“…For IVM and a few other anthelmintics, transcuticular-epidermal permeability had already been described by biophysical studies on cuticle–epidermis preparations of Ascaris suum and experiments using live A. suum with a surgically ligated pharynx [ 49 , 50 ]. Likewise, experiments in C. elegans have demonstrated a considerably quicker onset of pharyngeal paralysis in a cuticle defective C. elegans bus-8 loss-of-function strain [ 51 ]. A study by O’Lone and Campbell indicated that PP inhibition by refrigeration, and thus inhibition of oral ingestion, reduced the susceptibility to IVM in C. elegans [ 52 ].…”
Section: Discussionmentioning
confidence: 99%